Pembaruan Sistem Pemidanaan Pada Hukum Pidana Pidana Militer - Lubis, Arief Fahmi (STAI Bumi Silampari, 2022)
Renewing the Military Criminal Law Criminal System is not easy, especially the special criminal law system such as the Military Criminal Code (KUHPM), which is a codification of criminal law in the Criminal Code. The purpose of this study is to emphasize that the military criminal sanction system must still refer to the sanctions system in the Criminal Code (KUHP) or the Draft Criminal Code which is currently in the process of being drafted. Qualitative research uses a descriptive approach to collect data systematically, factually , and quickly according to the description when the research was conducted. The results of this study indicate that the guideline in the preparation of the Criminal Code is that punishment is an inseparable part of criminal law, so it is not a criminal law if it regulates only norms without being followed by criminal threats. Criminal threats that will be applied to criminal actors, although not primarily, but the nature of the crime is a crime